2022
DOI: 10.3389/fmicb.2022.950402
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the study of NADC34-like porcine reproductive and respiratory syndrome virus in China

Abstract: Since porcine reproductive and respiratory syndrome virus (PRRSV) was first described in China in 1996, several genetically distinct strains of PRRSV have emerged with varying pathogenicity and severity, thereby making the prevention and control of PRRS more difficult in China and worldwide. Between 2017 and 2021, the detection rate of NADC34-like strain in China increased. To date, NADC34-like strains have spread to 10 Chinese provinces and have thus developed different degrees of pathogenicity and mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The prevalence of HP-PRRSV has been seriously affecting the Chinese swine industry since 2006 [ 13 ]. Moreover, owing to the high rate of genetic evolution of PRRSV, the emergence of other PRRSV lineages (such as NADC30-like strains and NADC34-like strains) have also been documented in China in recent years [ 19 , 20 ]. Thus, investigating the epidemiological characteristics of PRRSV would be beneficial for PRRS control.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HP-PRRSV has been seriously affecting the Chinese swine industry since 2006 [ 13 ]. Moreover, owing to the high rate of genetic evolution of PRRSV, the emergence of other PRRSV lineages (such as NADC30-like strains and NADC34-like strains) have also been documented in China in recent years [ 19 , 20 ]. Thus, investigating the epidemiological characteristics of PRRSV would be beneficial for PRRS control.…”
Section: Discussionmentioning
confidence: 99%
“…The varia tion in the Nsp2 protein of the mutant strains mainly manifests as the "1+29" and "111+1+19"amino acid deletion patterns, similar to the highly pathogenic reference strains NADC30-like and JXA1 from lineages 1 and 8. This suggests the potential presence of highly pathogenic features in these mutant strains [39,40]. Interestingly, the absence of mutation at position 190aa contributed to its higher stability compared to position 63aa.…”
Section: Positive Selection Pressure and N-glycosylation Site Analysismentioning
confidence: 93%
“…Here, we selected sites that were identi ed as positive selection sites by all four methods. The results revealed that among all the isolated viral variant strains, PRRSV's GP5 protein had a total of 15 potential positive selection sites (11,18,19,20,33,38,39,40,65,109,111,131,158,199,203), PCV2's Cap protein had two potential positive selection sites (63, 109), while PCV3's Cap protein did not show any potential positive selection sites.…”
Section: Sequence Homology and Gene Recombination Analysismentioning
confidence: 99%
“…Subsequently, NADC34-like viruses were detected in Peru in 2015 [23] and in China in 2017 [24]. Since 2020, the NADC34-like PRRSVs have rapidly become prevalent in China [17,[25][26][27][28][29]. Te PRRSV strains circulating in Korea are mostly NADC30-like strains.…”
Section: Introductionmentioning
confidence: 99%